Comparative effect of Bharathanatyam and asana on the Flexibility among college students - Jothi, K.; Mangaiyakarasi, S.; Sabaananth, S. (University of Jaffna, 2011)
To achieve the purpose of this study, 45 women students were selected as subjects and their age were between 18-22 years. They were assigned into three groups of which one group served as bharathanatyam group, second group served as yoga asana training group and the third group served as control group. The subjects were selected at random. The interventional training programmes for this study were six weeks bharathanatyam for experimental group I and six weeks yoga asana training for experimental group II and the control group was not given any training except of the routine. Data were collected on the flexibility of the subjects before and after the training course were period of six weeks. Statistical treatment used was Analysis of Covariance (ANCOVA). In all the cases, 0.05 level of confidence was fixed to test the significance, which was considered as appropriate the results were subjected to post hoc analysis using Scheffe's Confidence Interval test. Within the limitations and delimitations set for this study, it was concluded, that Bharathanaiyam group significantly improved the flexibility of the subjects. Yogasana training Group significantly improved in flexibility, and Bharathanatyam training significantly improved flexibility than yogasana training group. Control group did not show any significant improvement.